P215 Left Ventricular Hypertrophy in Chronic Obstructive Pulmonary Disease Without Hypoxaemia: The Elephant in the Room?. (19th November 2012) - Anderson, WJ; Lipworth, BJ; Rekhraj, S; Struthers, AD; George, J
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is associated with significant cardiovascular mortality. Left ventricular hypertrophy (LVH) is a pivotal cardiovascular risk factor. The prevalence of LVH in COPD is currently unknown. Methods: We performed a pilot study of 93 normoxaemic COPD patients and 34 controls. Patients underwent echocardiography to measure left ventricular (LV) dimensions; electrocardiography; 24-hour blood pressure (BP) recording; and serum B-type natriuretic peptide (BNP) levels, along with spirometry and oxygen saturations. Results: COPD patients' oxygen saturations were normal at 96.5% (95%CI: 96.1–97.0%), with a mean FEV1 of 70.0% predicted (95% CI: 65.2–74.8%). 30.1% of COPD patients met echocardiographic criteria for LVH based on LV mass index, with more LVH in females than males (43.2% vs. 21.4%, p=0.02). LV mass index in COPD was 96.2g/m2 (95%CI: 90.1–102.7g/m2) vs. controls 82.9g/m2 (95%CI: 75.8–90.6g/m2), p=0.017 (Figure 1 ). LV mass index remained high in COPD patients in the absence of hypertension history (94.5g/m2 vs. 79.9g/m2, p=0.015) and with 24-hr systolic BP<135mmHg (96.7g/m2 vs. 82.5g/m2, p=0.024). LV ejection fraction (mean=63.4%) and BNP (mean=28.7pg/ml) were normal in COPD patients. Mean 24hr BP was normal in COPD patients at 125/72mmHg. Electrocardiography was less sensitive for detecting LVH than echocardiography. Conclusion: LVH was present in a significant proportion of normotensive, normoxaemic COPD patients, especially in females, along with normal LV ejection fraction and BNP levels. Clinical trials are therefore indicated to evaluate treatments to regress LVH in patients with COPD.